دور الإعلام المسموع في عملية التغييرالسياسي - كروشي, زكريا; مصباحي, بشير (جامعة الوادي - University of Eloued, 2022)
Summary : As a conclusion of the study, the audiovisual media have a major role in the process of political change, especially in the continuity of reform and awareness political work. Radio is also one of the main sources that contribute to the development of knowledge by providing taxi drivers and various groups of society with a great balance of knowledge and giving them positive attitudes towards it. Through our field and theoretical study, and through the results we obtained, we concluded that the audio media plays a major role in the process of political change, as the media play a prominent role in activating political participation and forming political awareness among members of society by developing their abilities to enter the political field. , whether participating in elections or entering political parties ... etc. The national radio also played a prominent role in the success of the electoral campaign through daily coverage of various gatherings or the interventions of parties over the air. In this regard, Radio Algiers in general and Radio El Oued in particular contributed and is still keeping pace with the electoral campaigns by programming special spaces such as “Legislative Discussion”, “Candidates Space”, “Women and Parliament” and others
د ا ر سة ميدانية على عينة من مستمعي إذاعة الواد ي
مذكرة ماستر إعلام وإتصال
Keywords: audio media, radio, political media, political change, national radio